2016
DOI: 10.4062/biomolther.2016.071
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Allergic Effect of Oroxylin A from Oroxylum indicum Using in vivo and in vitro Experiments

Abstract: Oroxylum indicum has long been used in Asian traditional medicine to prevent and treat respiratory diseases, diabetes, diarrhea and other conditions. Oroxylin A is a flavone that is present in Oroxylum indicum and in Scutellaria baicalensis. Because the root extracts of both plants have been shown to have anti-allergic effects, the authors investigated whether oroxylin A is likely to have beneficial effects on allergic asthma using female Balb/c mice and rat RBL-2H3 mast cells. Antigen-induced degranulation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 34 publications
1
15
0
1
Order By: Relevance
“…This study also supports the previous experiment as simvastatin was treated as a very potential lipid-lowering drug and coincided with prior studies [102][103][104][105][106]. To identify the level enzymes (both SGPT and SGOT) both treatment protocols failed to decrease the level of specific enzyme level to a noteworthy extent and exhibited similarities with past studies [107][108][109][110][111][112][113] but revealed satisfactory decline. Liver enzymes SGPT and SGOT are considered as surrogate markers of diabetes mellitus complication.…”
Section: Discussionsupporting
confidence: 89%
“…This study also supports the previous experiment as simvastatin was treated as a very potential lipid-lowering drug and coincided with prior studies [102][103][104][105][106]. To identify the level enzymes (both SGPT and SGOT) both treatment protocols failed to decrease the level of specific enzyme level to a noteworthy extent and exhibited similarities with past studies [107][108][109][110][111][112][113] but revealed satisfactory decline. Liver enzymes SGPT and SGOT are considered as surrogate markers of diabetes mellitus complication.…”
Section: Discussionsupporting
confidence: 89%
“…Synthesized cDNA products, primers for each gene, and Promega Go‐Taq DNA polymerase (Madison, WI) were used for PCR. Specific primers and PCR conditions were as previously described (Lee, Kang, Park, Huang, & Im, ; Park et al, ). Aliquots (7 μl) were electrophoresed in 1.2% agarose gels and stained with StaySafe ™ Nucleic Acid Gel Stain (Real Biotech Corporation, Taipei, Taiwan; Kang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…We gathered three extracts that associated with this process: Oroxylin A [ 43 ], Bakkenolide B [ 66 ], and Petatewalide B [ 67 ]. The first one is isolated from Scutellaria baicalensis while the next two are from Petasites japonicus .…”
Section: Basic Researchesmentioning
confidence: 99%